Social Support and Resilience to Students Who Are Working on Thesis - Maria Foni Bule; Luh Putu Ruliati; Juliana M.Y Benu (Journal of Health and Behavioral Science, 2021)
Abstract.Students working on their thesis experience many obstacles and problems that make them not complete assignments on time. The problems they experience can be overcome if they have a high level of resilience and receive support around them. This study aims to determine the relationship between social support for students who are working on their thesis at FKIP Undana Kupang. This research is a quantitative study using a correlational method. The population in this study was 278 students of class 2015/2016 who are actively working on their thesis with a sample size of 100 students. The analysis in this study used Pearson correlation analysis. The results of the study resulted in a rxy of 0.555 with a value (sig) = 0.000 <0.05, which means that there is a positive relationship between social support and resilience in students who are working on their thesis, the higher the social support provided, the higher the resilience of students.